An Overview of the Pharmacokinetics and Pharmacodynamics of Landiolol (an Ultra-Short Acting β1 Selective Antagonist) in Atrial Fibrillation - Mariana Floria; Alexandru Florinel Oancea; Paula Cristina Morariu; Alexandru Burlacu; Diana Elena Iov; Cristina Petronela Chiriac; Genoveva Livia Baroi; Celina Silvia Stafie; Magdalena Cuciureanu; Viorel Scripcariu; Daniela Maria Tanase (MDPI AG, 2024)
Landiolol is an ultra-short-acting, selective β1-adrenergic receptor blocker that was originally approved in Japan for the treatment of intraoperative tachyarrhythmias. It has gained attention for its use in the management of tachyarrhythmias and perioperative tachycardia, especially atrial fibrillation for both cardiac and non-cardiac surgeries. It can be the ideal agent for heart rate control due to its high β1-selectivity, potent negative chronotropic effect, a limited negative inotropic potential, and an ultrashort elimination half-life (around 4 min); moreover, it may have a potential therapeutic effects for sepsis and pediatric patients. Landiolol seems to be superior to other short-acting and selective beta-blockers such as esmolol. This review aims to provide a comprehensive overview of landiolol, a new ultra-short-acting β1 selective antagonist, including its pharmacology, clinical applications, efficacy, safety profile, and future directions in research and clinical data.